Method for evaluating the performance of antiskid devices - I. A. Zharov; A. A. Alekseev (Вестник Научно-исследовательского института железнодорожного транспорта)
To detect the beginning of the entry of the wheelset in the skid, it is necessary to know the angular velocity of rotation of the wheelset, which is usually measured by a pulse speedometer. Usually, magnetic sensors are used for this purpose (the voltage pulse appears when the magnet passes the coil) or optoelectronic (voltage pulse appears when the light beam passes through the slot and hits it on the photodiode). Between the voltage pulses, the point on the rolling surface of the wheel passes the path Δ x . Processing pulses can be different. In this paper considers the case when the number of pulses is counted with the periodicity Δ t . In this work, the following is additionally done: - A calculation method is proposed that finds the limit of the performance of an antiskid device with specified parameters. At the same time, the time required to detect the beginning of the entry into skid is taken into account. - Earlier it was established that the most stringent requirements for the parameters of antiskid devices are at the end of braking because of the easy entry into the skid at low speeds. Therefore, the question was studied on how much the braking coefficient of coupling of the wheelset Ψ0 (the ratio of the braking force to the load per axle) should be reduced at low speeds so as to eliminate the possibility of damage to the wheels when entering the skid. - It is discussed how it is possible to determine the parameters of antiskid devices during braking tests of rolling stock and how to use these calculated dependencies in these tests. From the existing methods of testing antiskid devices, this approach is different in that the performance of an antiskid device is evaluated not on a specific segment of the track with reduced cohesion, but on the estimated track with the worst coefficient of adhesion at each point (the shorter the track section, the faster the wheelset enters the skid, but it is also more difficult to damage it). The article suggests a method for antiskid devices of railway rolling stock, which allows calculating how to reduce the braking force at the end of braking and to estimate the growth of the braking distance due to this. The method allows estimating how much the growth of the braking distance of this train due to this reduction depends on the parameters of the antiskid devices.